QUICK RESPONSE CODE PADA SISTEM INFORMASI KEHADIRAN GURU DAN SISWA SMK NURUL MUHTADIN - R Kania; Khasan Asrori; Haris Setiawan; Anna Rosdiana (Jurnal Ilmiah Sains dan Teknologi, 2023)
Attendance is an activity that must be carried out in various activities, one of which is in teaching and learning activities in schools, lectures, seminars, meetings, teacher attendance, and others. In teaching and learning activities in schools and terms of teacher absenteeism, attendance is an important parameter because it can affect student success and teacher performance in the continuity of teaching and learning activities, especially at SMK Nurul Muhtadin Kibin. At this time, the attendance system at SMK Nurul Muhtadin Kibin school attendance activities for teachers and students is still using the conventional way, namely the teacher in the class mentions the names of students one by one and then puts a dot on the attendance book for each class that has been prepared by the school and for attendance teachers have administrative officers who go around checking each class by using paper as a medium for recording teacher absences. This method is certainly very risk when the attendance book is lost or damaged so that the loss of attendance information that has been carried out, as well as for making teacher attendance reports takes a little longer and risks errors in reporting teacher absenteeism. The use of QR CODE in the development of a web-based Teacher and Student Attendance Information System is expected to solve existing problems. The system that built by this author uses the PHP version 7 programming language, MySQL as the database media. The development method that will be used by the author is to use the Waterfall method. With the presence of a teacher and student attendance information system using this QR Code, the author to overcome the problems faced by making it easier for students and teachers who want to take attendance.